ANALISIS STILISTIKA PADA CERPEN “KUTUKAN DAPUR” KARYA EKA KURNIAWAN - Lasenna Siallagan; Hodtua Lestari Rajagukguk3; Elsa Mayora; Kartika Bestari (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This research was carried out based on the curiosity of researchers towards Stalistic Analysis in a short story by Eka Kurniawan entitled "Kitchen Curse". The method used in this research is descriptive qualitative method. The purpose of this study is to find out which language styles are contained in the short story "Kitchen Curse" by Eka Kurniawan. The research technique that researchers use is literature study. Literature study is done by reading various library materials that are closely related to the problem to be studied. Through a stylistic approach, the author examines some of the phenomena mentioned above, especially those related to human life events. The results of this study found four language styles in the short story entitled "Kitchen Curses" The language styles are, opposing language style, comparative language style, linking language style, and repetition language style.